Using fuzzy logic in the governing system of a micro-hydro power plant - Gan Lim, Laurence A. (Animo Repository, 2001)
This is a study of the implementation of fuzzy logic control in micro-hydro power stabilization. The focus of the study is on a generator that is driven by a cross-flow turbine operating with two flow-control guide vanes. No attempt is made to investigate on other turbine-generator set-up for comparative study. Two parameters, the turbine speed and generator output voltage, are controlled in order to regulate the generator output power. A large part of this study involved the assembly of the electronic hardware that was necessary to implement fuzzy logic control. The method by which the author was able to implement fuzzy logic control was presented in this thesis. The scheme in controlling the two flow-control guide vanes was the key in the regulation of the turbine speed. The generator output voltage was regulated by controlling the excitation field voltage of the generator. The performance of the fuzzy logic controller was evaluated by analyzing the turbine speed and generator output graphs both as functions of time. Three trials were conducted in order to compare the effectiveness of the fuzzy logic controller that was developed in this study. The results of the performance tests showed that the fuzzy logic controller that was developed in this study was effective in stabilizing the generator output voltage and the turbine speed.